Smartphones, women’s rights and coupons: New trends that can boost insurance for African farmers - Kramer, Berber; Hill, Ruth Vargas (The Conversation, 2025)
This piece on "The Conversation" highlights how emerging innovations in technology, product design and gender inclusion can expand access to agricultural insurance for smallholder farmers across Africa. As climate change intensifies droughts, floods and other weather extremes, smallholders remain highly exposed, yet traditional insurance models have struggled to reach them due to high costs, limited trust and administrative challenges. The authors discuss how smartphone-based photo verification can simplify loss assessment, how insurance “coupons” can make premiums more affordable at the point of purchase, and how strengthening women’s rights and decision-making power can increase both uptake and the equitable distribution of benefits. They also underscore the value of complementing formal insurance with existing informal risk-sharing networks. Together, these innovations can lower barriers to participation, reduce basis risk, and create more inclusive insurance markets, which will help scale climate-risk protection across the continent.